Probing the Electrostatic Barrier of Tetrathiafulvalene Dications using a Tetra‐stable Donor–Acceptor [2]Rotaxane. Issue 28 (28th April 2020) - Jensen, Morten; Kristensen, Rikke; Andersen, Sissel S.; Bendixen, Dan; Jeppesen, Jan O.
Abstract: A tetra‐stable donor–acceptor [2]rotaxane 1 ⋅4PF6 has been synthesized. The dumbbell component is comprised of an oxyphenylene (OP), a tetrathiafulvalene (TTF), a monopyrrolo‐TTF (MPTTF), and a hydroquinone (HQ) unit, which can act as recognition sites (stations) for the tetra‐cationic cyclophane cyclobis(paraquat‐ p ‐phenylene) (CBPQT 4+ ). The TTF and the MPTTF stations are located in the middle of the dumbbell component and are connected by a triethylene glycol (TEG) chain in such a way that the pyrrole moiety of the MPTTF station points toward the TTF station, while the TTF and MPTTF stations are flanked by the OP and HQ stations on their left hand side and right hand side, respectively. The [2]rotaxane was characterized in solution by 1 H NMR spectroscopy and cyclic voltammetry. The spectroscopic data revealed that the majority (77 %) of the tetra‐stable [2]rotaxane 1 4+ exist as the translational isomer 1 ⋅MPTTF 4+ in which the CBPQT 4+ ring encircles the MPTTF station. The electrochemical studies showed that CBPQT 4+ in 1 ⋅MPTTF 4+ undergoes ring translation as result of electrostatic repulsion from the oxidized MPTTF unit. Following tetra‐oxidation of 1 ⋅MPTTF 4+, a high‐energy state of 1 8+ was obtained (i.e., 1 ⋅TEG 8+ ) in which the CBPQT 4+ ring was located on the TEG linker connecting the di‐oxidized TTF 2+ and MPTTF 2+ units. 1 H NMR spectroscopy carried out in CD3 CN at 298 K on a chemically oxidized sample of 1 ⋅MPTTF 4+ revealed that the metastable state 1 ⋅TEG 8+ is only short‐lived with a lifetime of a few minutes and it was found that 70 % of the positively charged CBPQT 4+ ring moved from 1 ⋅TEG 8+ to the HQ station, while 30 % moved to the much weaker OP station. These results clearly demonstrate that the CBPQT 4+ ring can cross both an MPTTF 2+ and a TTF 2+ electrostatic barrier and that the free energy of activation required to cross MPTTF 2+ is ca. 0.5 kcal mol −1 smaller as compared to TTF 2+ . Abstract : A tetra‐stable donor–acceptor [2]rotaxane, composed of an oxyphenylene (OP), a tetrathiafulvalene (TTF), a monopyrrolo‐TTF (MPTTF), and a hydroquinone (HQ) unit in the dumbbell component and encircled by the tetra‐cationic cyclophane cyclobis(paraquat‐ p ‐phenylene) (CBPQT 4+ ) was used to probe the electrostatic barriers for the movement of CBPQT 4+ across an MPTTF 2+ and a TTF 2+ dication.